Analisis Struktur Modal PT Unilever Indonesia dan PT Mayora Indah - Emilda, Emilda (MOTIVASI, 2018)
ABSTRACT Purpose - This study aims to determine the financial and operational characteristics of both companies, analyzing the capital structure policy and analyze whether differences in performance caused by the company's capital structure policy, and to analyze the presence or absence of financial leverage on PT Mayora Indah which use high levels of debt. Design/methodology - he research methodology used in this research is quantitative research with explanatory type. The data type used secondary data in the form of financial statements, inflation rate, BI rate and exchange rate. The data analysis used financial statements and financial ratios.Findings – PT Unilever Indonesia has a policy of capital structure with 100% equity, while PT Mayora Indah has capital structure in the form of high proportion of debt levels. Theoretically characteristics of a company has a role in influencing the capital structure and the capital structure of a company is one of the factors that affect the company's performance. The analysis results indicate that the company's financial performance is not resulted from the capital structure policy. It is seen from the ratio chart of OPM and NPM having similar direction of high debt movement and the use of high debts at PT Mayora Indah does not generate financial leverage